Fuzzy logic control of active and reactive power for a grid-connected photovoltaic system using a three-level neutral-point-clamped inverter - Ghrissi Tahri; Zoubir Ahmed Foitih; Ali Tahri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper aims to present a fuzzy logic control (FLC) of active and reactive power for a grid-connected photovoltaic system. The PV system is connected to the grid utility using a three-level neutral point clamped inverter (3L-NPC) and LCL filter. Two control strategies, fuzzy logic control, and conventional PI control are applied. The design of the two control strategies is based on calculating the instantaneous active and reactive power from the measured grid voltages and currents to allow the system to have a dynamic robustness performance against a sudden change in reactive power and satisfactory active power tracking under rapid solar radiation changes. The control strategies can transfer the total active power generated by the PV array to the grid utility with high power quality and a unity power factor. The simulation results using the Matlab-Simulink environment show that the FLC strategy has a better dynamic performance with less settling time, and overshoot compared to the conventional PI control.